The Recontruction of Pancasila Value Based Character Education Through the Curriculum of Love - Dalila, Alfa; Fa’atin, Salmah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Indonesia, particularly in relation to moral degradation, declining social empathy, and the increasing tendency toward individualism among students, highlighting the need for a more holistic approach to character education grounded in Pancasila values. This study aims to reconstruct Pancasila-based character education through the Curriculum of Love as an alternative framework that emphasizes affective, relational, and humanistic dimensions of learning. Employing a qualitative research design within an interpretive paradigm, the study utilizes in-depth interviews, observations, and document analysis, with data analyzed. The findings reveal that the Curriculum of Love enables the meaningful internalization of Pancasila values by integrating compassion, empathy, mutual cooperation, tolerance, and social justice into everyday educational practices, fostering positive pedagogical relationships and inclusive learning environments. Teachers play a pivotal role as moral exemplars and facilitators who embody Pancasila values through caring interactions and reflective teaching strategies. The study concludes that the reconstruction of character education through the Curriculum of Love transforms Pancasila values from abstract normative concepts into lived educational experiences, offering a promising paradigm for strengthening character formation and promoting socially responsible, empathetic, and morally grounded students within contemporary Indonesian education.